An Analysis of Humanism Values in the Bidadari Terakhir Novel by Agnes Davonar - Ida Sukowati; Yessy Soniatin; Zeni Irawati Fadhilah; Fransiska Angela Larasati; Adinda Victoryah Wahyuningtyas (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
This study discusses the social values ​​of humanism contained in the novel Bidadari Terakhir by Agnes Davonar. The discussion is carried out using a sociological review of literature, to be able to find out the problems that show the relationship between humans in the novel. This study is intended to reveal (1) describe the love and affection of the main character in Agnes Davonar's Bidadari Terakhir Novel, (2) describe the sacrifices experienced by the main character in Agnes Davonar's Bidadari Terakhir Novel, (3) describe long-distance communication media. by the main character in Agnes Davonar's novel Bidadari Akhir. The type of research used in this study is a qualitative method. The data in this study are in the form of data in the form of quotations, expressions and images that contain the social values ​​of humanism. The data collection technique used in this research is the note-taking technique. The data analysis technique used in this research is descriptive analysis. The humanism values were seen in the picture of love between fellow human beings, both love for family and love for lovers, sacrifices made by someone for the most important person in his life. Communication media is also a support for human interaction to be easy.